Development of Vibrio parahaemolyticus sensitive and specific loop-mediated isothermal amplification combined with lateral flow device - Liang, Xiaoheng; Zhan, Dan; Huang, Xin; Bi, Jinli; Li, Jinghan; Meng, Liqin; Xie, Li; Li, Taijie (Biomedical papers, 2025)
Background and Aim. Vibrio parahaemolyticus a gram-negative, rod-shaped bacterium with salinophilic properties is found mainly in rivers, oceans, and coastal environments. With the expanding scale of aquaculture in coastal regions of China, the contamination of seafoods with Vibrio parahaemolyticus is becoming a significant cause of food poisoning with symptoms including gastroenteritis, wound infection and sepsis. Current methods for detecting this microorganism are unsuitable in the present context. We developed a rapid LAMP-LFD method-by combining the loop-mediated isothermal amplification technique (LAMP) and lateral flow device (LFD).Methods. The thermolabile hemolysin tlh gene of Vibrio parahaemolyticus was used as the target, and we designed five specific primers in its conserved region. The primers were used to carry LAMP reaction with biotin labelling, the products completed hybridisation with the FAM-labelled primers, and the hybridisation products were tested for results on LFD.Results. The results showed that the LAMP-LFD method specifically detected Vibrio parahaemolyticus and was negative for proximate strains such as Vibrio vulnificus and other Vibrio pathogens as well as common pathogens such as Escherichia coli. The optimised reaction conditions for LAMP were 40 min at 60 °C, plus 5 min of probe hybridisation and 3-5 min of LFD color development. The lowest concentration of Vibrio parahaemolyticus pure culture bacterial fluid of 1.5*102 cfu/mL could be detected, and the pathogen could be detected from tissue samples with a contamination concentration of 0.75*103 cfu/mL. The method has higher specificity and sensitivity, and the pathogen can be detected within 1.5 h.Conclusion. The LAMP-LFD method for Vibrio parahaemolyticus established in this study has the advantages of convenient operation, low dependence on equipment, high sensitivity and rapid detection, all of make it ideally suited to the detection of Vibrio parahaemolyticus at the grass-roots level.
Keywords: Vibrio parahaemolyticus; loop-mediated isothermal amplification; tlh gene; LFD